Comparison of the Chemical Profiles and Antioxidant Activities of Different Parts of Cultivated Cistanche deserticola Using Ultra Performance Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometry and a 1,1-Diphenyl-2-picrylhydrazyl-Based Assay - Xiaoming Wang; Jinfang Wang; Huanyu Guan; Rong Xu; Xiaomei Luo; Meifeng Su; Xiaoyan Chang; Wenting Tan; Jun Chen; Yue Shi (Molecules, 2017)
In this study, a sensitive ultra-performance liquid chromatography-photodiode array coupled to quadruple time-of-flight mass (UPLC-PDA-Q/TOF-MS) method and a 1,1-diphenyl-2- picrylhydrazyl (DPPH)-based assay were used to determine the chemical constituents and screen the antioxidant activity profiles of the methanol extracts of different parts of cultivated Cistanche deserticola (C. deserticola). First, qualitative and quantitative chemical composition analyses of the different parts of cultivated C. deserticola were conducted. Obvious differences were observed between the chemical profiles and content distribution of phenylethanoid glycosides (PhGs) from the different cultivated C. deserticola parts. The average contents of the six PhGs parts varied from 4.91 to 72.56 mg/g DW (milligrams of extract per gram of plant dry weight) in the six different parts of Cistanche deserticola, displaying a significant decreasing trend from the bottom to the top of cultivated C. deserticola and the highest content in the stems. From the bottom to the top of the plant, the echinacoside and cistanoside A content decreased and the 2 ′ -acetylacteoside content increased. Second, an offline DPPH assay revealed that the total scavenging activities of all parts within the range of 20–500 μ g/mL increased in a concentration-dependent manner and that good antioxidant activities were found in all plant parts, particularly in the stems, which could be related to their higher PhG content. Additionally, a DPPH-UPLC-PDA method was successfully applied to rapidly screen the antioxidant profiles and antioxidant components of the different cultivated C. deserticola parts. According to the antioxidant profiles before and after the DPPH reaction, there were wide variations in the antioxidant activities of different cultivated C. deserticola parts. Moreover, the antioxidant profiles revealed the presence of major free radical scavengers identified as PhGs using UPLC-Q/TOF-MS. Finally, the established DPPH-UPLC-PDA method was reagent saving, rapid and feasible for correlating the chemical profile of traditional chinese medicines (TCMs) with their bioactivities without isolation and purification and may be used for multicomponent analysis of active substances in other foods and herbs. Therefore, to better harness C. deserticola resources, using this method to evaluate cultivated C. deserticola, a promising herb material with obvious antioxidant activity, is crucial.